2021
DOI: 10.1007/s10479-021-04075-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid PSO-based metaheuristic for costly portfolio selection problems

Abstract: In this paper we propose a hybrid metaheuristic based on Particle Swarm Optimization, which we tailor on a portfolio selection problem. To motivate and apply our hybrid metaheuristic, we reformulate the portfolio selection problem as an unconstrained problem, by means of penalty functions in the framework of the exact penalty methods. Our metaheuristic is hybrid as it adaptively updates the penalty parameters of the unconstrained model during the optimization process. In addition, it iteratively refines its so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 68 publications
(89 reference statements)
0
17
0
Order By: Relevance
“…We first point out the strengths and weaknesses of using the proposed algorithm to tackle large-scale cardinality-constrained portfolio optimization problems. The comparisons are made with two recent variants of the LLSO as well as with other state-of-the-art swarm optimization algorithms implementing the exact 1 -penalty function approach proposed in [15]. Finally, we assess the profitability of the investment strategy in a real-world case study by varying the size of portfolios.…”
Section: Experimental Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…We first point out the strengths and weaknesses of using the proposed algorithm to tackle large-scale cardinality-constrained portfolio optimization problems. The comparisons are made with two recent variants of the LLSO as well as with other state-of-the-art swarm optimization algorithms implementing the exact 1 -penalty function approach proposed in [15]. Finally, we assess the profitability of the investment strategy in a real-world case study by varying the size of portfolios.…”
Section: Experimental Analysismentioning
confidence: 99%
“…In the previous subsection, we have analysed the impact of the mutation on the capabilities of LLSObased algorithms, finding that the ALLSO-MUT-H is the more efficient choice in terms of convergence and quality of solutions. Now, the aim is to compare the above quoted optimizer with other stateof-the-art swarm optimization algorithms, namely the PSO [15] and the Firefly algorithm (FA) [49], both endowed with an exact 1 -penalty function. In this regard, the literature presents a wide range of penalty methods to tackle constraint-handling problems [33].…”
Section: Comparison With State-of-the-art Swarm Optimization Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid models are also demonstrated that combine learning-based systems with the sentiments in the unstructured non-numeric contents on the social web [8][9]. The use of multi-objective optimization, principal component analysis, and metaheuristics have also been proposed by some researchers in portfolio design [10][11][12]. Estimating volatility in future stock prices using GARCH has also been proposed in some work [13].…”
Section: Related Workmentioning
confidence: 99%
“…Meta-heuristic algorithms have been widely used in all aspects of social production and life. Many related research papers are published every year in the fields of production scheduling [14,15], engineering computing [16,17], management decision-making [18,19], machine learning (ML) [20,21], system control [22], and many other disciplines.…”
Section: Of 41mentioning
confidence: 99%